Dexmedetomidine versus Clonidine as Intrathecal Adjuvants to Hyperbaric Ropivacaine for Subarachnoid Block in Patients with History of Scorpion Bite undergoing Infraumbilical Surgery: A Double-blinded Randomised Clinical Study - Mouna Rao; Naseema V Kanase; Namrata Mandirwala; Neha Manoj Kushe (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Patients with previous scorpion sting may show variable response to spinal local anaesthetics because scorpion toxins can alter voltage-gated sodium-channel behaviour. Ropivacaine and intrathecal alpha-2 agonists may improve block reliability in this subgroup. Aim: To compare intrathecal dexmedetomidine and clonidine as adjuvants to 0.75% hyperbaric ropivacaine for Subarachnoid Block (SAB) in patients with history of scorpion bite undergoing infraumbilical surgery. Materials and Methods: This double-blinded randomised clinical study was conducted in the Department of Anaesthesiology, Krishna Vishwa Vidyapeeth (Deemed to be University), Karad, Maharashtra, India. The study included 78 American Society of Anaesthesiologists (ASA) I-II adults aged 18-60 years with documented scorpion bite history scheduled for elective infraumbilical surgery. Patients were allocated equally. Group RD received 3 mL 0.75% hyperbaric ropivacaine with dexmedetomidine 5 µg intrathecally, while Group RC received 3 mL 0.75% hyperbaric ropivacaine with clonidine 30 µg. Block characteristics, block success and haemodynamic variables were recorded. Normality was assessed using the Shapiro-Wilk test. Continuous variables were compared using the independentsamples t-test, and categorical variables using the Chi-square or Fisher’s exact test. A p-value